1981
DOI: 10.1295/polymj.13.51
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Reaction between Neighboring Substituents of Specially-Designed Alternating Copolymers

Abstract: ABSTRACT:The maximum conversion of an intramolecular reaction between neighboring substituents on specially-designed alternating copolymers was calculated theoretically. The terpolymer of monomers A, D1, and D2 , were supposed to consist of two alternating units, A-D1 and A-D2, distributed in a certain statistical state. In such a modified alternating copolymer, substituent X on unit A was permitted to perform the intramolecular reaction only with substituent Y1 on unit D1, not with Y2 on D2 . As a result, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As was shown theoretically in the preceding papers, 7 the intramolecular reactions between D 1 and A units of the specially-designed alternating copolymer of D1, D 2 , and A monomers are capable of exceeding the Flory's limit. In this paper, we carried out the ternary copolymerization of VOSi, St, and MA or PhA and the hydrolysis and lactonization of VOSi units of the copolymers.…”
Section: Lactonizationmentioning
confidence: 58%
See 1 more Smart Citation
“…As was shown theoretically in the preceding papers, 7 the intramolecular reactions between D 1 and A units of the specially-designed alternating copolymer of D1, D 2 , and A monomers are capable of exceeding the Flory's limit. In this paper, we carried out the ternary copolymerization of VOSi, St, and MA or PhA and the hydrolysis and lactonization of VOSi units of the copolymers.…”
Section: Lactonizationmentioning
confidence: 58%
“…According to Flory's statistical considerations, 6 however, even an alternating copolymer can not In the preceding paper, 7 the authors showed theoretically that the substituents of a speciallydesigned alternating copolymer could undergo 100% intramolecular reaction beyond the so-called Flory's limit. In order to show an experimental example of such a copolymer, we consider trimethylvinyloxysilane to be important.…”
mentioning
confidence: 99%
“…Thus, the copolymers la in this paper can be regarded as a profitable model for a "specially-designed alternating copolymer". 28 IR analysis of la after desilylation clarified the geometrical structure of the silyloxy diene unit in the copolymer la quantitatively according to the same method…”
mentioning
confidence: 99%
“…We have already demonstrated successful cases in which specially-designed alternating copolymers have been employed for this purpose. 5…”
mentioning
confidence: 99%